Direct Growth of Si, Ge, and Si–Ge Heterostructure Nanowires Using Electroplated Zn: An Inexpensive Seeding Technique for Li‐Ion Alloying Anodes. Issue 10 (21st January 2021) - Kilian, Seamus; McCarthy, Kieran; Stokes, Killian; Adegoke, Temilade Esther; Conroy, Michele; Amiinu, Ibrahim Saana; Geaney, Hugh; Kennedy, Tadhg; Ryan, Kevin M.
Abstract: A scalable and cost‐effective process is used to electroplate metallic Zn seeds on stainless steel substrates. Si and Ge nanowires (NWs) are subsequently grown by placing the electroplated substrates in the solution phase of a refluxing organic solvent at temperatures >430 °C and injecting the respective liquid precursors. The native oxide layer formed on reactive metals such as Zn can obstruct NW growth and is removed in situ by injecting the reducing agent LiBH4 . The findings show that the use of Zn as a catalyst produces defect‐rich Si NWs that can be extended to the synthesis of Si–Ge axial heterostructure NWs with an atomically abrupt Si–Ge interface. As an anode material, the as grown Zn seeded Si NWs yield an initial discharge capacity of 1772 mAh g −1 and a high capacity retention of 85% after 100 cycles with the active participation of both Si and Zn during cycling. Notably, the Zn seeds actively participate in the Li‐cycling activities by incorporating into the Si NWs body via a Li‐assisted welding process, resulting in restructuring the NWs into a highly porous network structure that maintains a stable cycling performance. Abstract : Zn seeds are deposited on stainless steel using a low‐energy electroplating technique which directly catalyzes Si, Ge, and Si–Ge axial heterostructure nanowires in a glassware‐based synthesis approach. The Si nanowires exhibit an initial discharge capacity of 1772 mAh g −1 and a capacity retention of 85% after 100 cycles resulting in the formation of a stable Zn–Si alloy.